Evaluating the karyotypic diversity in species of Hyla (Anura, Hylidae) with 2n = 30 chromosomes based on the analysis of ten species - Gruber, S. L. [UNESP]; Haddad, C. F B [UNESP]; Kasahara, Sanae [UNESP] (My University, 2005)
Ten species of Hyla with 2n = 30 from Brazilian fauna were analysed cytogenetically. Hyla minuta is the unique presenting all bi-armed metacentric or submetacentric chromosomes in the karyotype, therefore, with the highest FN = 60. The remaining species have a variable number of uni-armed telocentric or subtelocentric chromosomes: H. cruzi, H. elianeae, and H. rubicundula with three pairs (FN = 54), H. berthalutzae, H. elegans, H. microps, and H. nana with four pairs (FN = 52), and H. nahdereri and H. sanborni with five pairs (FN = 50). The uni-armed elements are among pairs 5, 6, 7, 11, 14, and 15, which also appeared with metacentric or submetacentric morphology. The remaining chromosome pairs 1, 2, 3, 4, 8, 9, 10, 12, and 13 were never found to be telocentric or subtelocentric. AgNOR patterns are species-specific, the majority of the species exhibiting a single pair with AgNORs, with the exception of H. elegans and H. nana with more than one chromosome pair bearing this cytological marker. C banding was obtained in H. berthalutzae, H. cruzi, H. elegans, H. elianeae, H. microps, H. minuta, H. nahdereri, and H. nana, which showed positively stained centromeric heterochromatin. Our analysis confirms the great karyotypic diversity in the species of Hyla with 2n = 30, with no species sharing identical karyotypes.
Keywords: Amphibian; Chromosome banding; Karyotype; Taxonomy; Amphibia; Brazil; centromere; chromosome banding pattern; chromosome map; chromosome NOR; cytogenetics; fauna; genetic variability; hyla; karyotype; nonhuman; phylogeny; species difference; taxonomy; Animals; Anura; Chromosome Banding; Chromosomes; Karyotyping; Metaphase; Species Specificity; Hyla; Hyla elegans; Hyla minuta; Hylidae